2021
DOI: 10.1021/acs.jpclett.1c02789
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the Origin of Vibrational Coherence Transfer Between the S1 and T1 States of the Pt-pop Complex

Abstract: We demonstrate that spin-vibronic coupling is the most significant mechanism in vibrational coherence transfer (VCT) from the singlet (S 1 ) to the triplet (T 1 ) state of the [Pt 2 (P 2 O 5 H 2 ) 4 ] 4− complex. Our time-dependent correlation function-based study shows that the rate of intersystem crossing (k ISC ) through direct spin−orbit coupling is negligibly small, making VCT vanishingly small due to the ultrashort decoherence time (2.5 ps). However, the inclusion of the spin-vibronic contribution to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…The transfer of vibrational coherence between different electronic states was recently observed in transition metal complexes after ultrafast intersystem crossing. 91,92 As discussed below, our experimental results favor the mechanism involving vibrational coherence transfer.…”
Section: Vibrational Wave Packet Dynamics Induced By the Photoionizat...supporting
confidence: 67%
“…The transfer of vibrational coherence between different electronic states was recently observed in transition metal complexes after ultrafast intersystem crossing. 91,92 As discussed below, our experimental results favor the mechanism involving vibrational coherence transfer.…”
Section: Vibrational Wave Packet Dynamics Induced By the Photoionizat...supporting
confidence: 67%
“…They have observed that this coupling vector largely depends on the nature of the two triplet or singlet states and the energy gap between them. On the other hand, Marian et al 65 and Karak et al 68 have considered the spin-vibronic interaction through the explicit calculation of the derivative of the direct SOC with respect to the normal mode coordinates and successfully applied the method for calculating the rate constant of intersystem crossing. Nevertheless, in the present work, we have adopted the method developed by Kim et al 26 .…”
Section: Introductionmentioning
confidence: 99%
“…A variable we have proposed that may serve as a means of differentiating active versus spectator modes is the dephasing time of the coherence. 11–13 Upon excitation with a sufficiently short laser pulse, the initial excited state is characterized by a coherent superposition of vibrational states that are all phase-locked; the motion of this wavepacket is what gives rise to the oscillations shown in Fig. 3 and described by eqn (1).…”
Section: Resultsmentioning
confidence: 99%